PENGEMBANGAN APLIKASI TERINTEGRASI BERBASIS WEIGHTED MOVING AVERAGE DAN METODE AVERAGE UNTUK PERAMALAN PERSEDIAAN DAN HARGA POKOK PENJUALAN - Triana Sri Gunarti; Baibul Tujni; Imam Solikin (Jurnal Sistem Informasi dan Informatika (Simika), 2026)
This study aims to design and implement an integrated application for inventory forecasting using the Weighted Moving Average (WMA) method and cost of goods sold calculation using the Average method at TB Amanda, a company engaged in building material sales. The WMA method is applied to forecast future inventory requirements based on weighted historical sales data, while the Average method is used to calculate the cost per unit of inventory based on the weighted average of available stock costs. The system was developed using a structured software development approach and evaluated through functional testing and accuracy testing of forecasting results. The evaluation shows that the implemented WMA method produces forecasting results with a good level of accuracy, while the Average method generates cost of goods sold values that are consistent with manual calculations. In addition, the integrated system is able to automate transaction recording, inventory updating, forecasting, and cost calculation in a single database. These results indicate that the proposed application can support inventory planning and cost calculation processes at TB Amanda more systematically and accurately.